MANAJEMEN SDM DALAM PENDIDIKAN : UPAYA PENGELOLAAN SUMBER DAYA MANUSIA DI SEKOLAH - Haratua, Chandra Sagul; Utami, Citra Widuri Nur Fajar; Kloudya, Mira; Sari, Inta Jukanti; Fitriyani, Nunu (Jurnal Dedikasi Pendidikan, 2025)
Human resources (HR) are the most valuable assets in an organization, including in the education sector. Effective Human Resource Management can support the achievement of educational goals, both short and long term goals. Management within the school environment must involve important elements, namely educators and educational staff so that it can be ensured that there are competent, motivated and in line with the vision and mission of the institution. By using a literature review method, this journal aims to explore the concepts and practices of Human Resource Management in the school environment, as well as identifying Human Resource management efforts that can help educational institutions achieve their goals. The discussion will cover key aspects of Human Resources Management such as developing the competence of teaching staff, establishing a conducive work culture, implementing technology in managing human resources, and improving the welfare of Human Resources. It is hoped that this journal can provide insight and recommendations for educational practitioners in managing Human Resources in the school environment strategically.